Rancang Bangun Konsentrator Oksigen Menggunakan 4 Bahan Filtrasi Sebagai Alternatif Alat Bantu Pernafasan - Dimas Ricky Saputra; Kristianto Wahyu Lestari; Akbar Sujiwa (FORTEI Regional VII Jawa Timur, 2022)
E Along with the development of the Covid-19 pandemic, the need for oxygen is also increasing rapidly. More and more people are in need of oxygen cylinders, but the amount available is not enough to meet the needs of the winder community. Oxygen Concentrator is a device capable of up to 95% using Pressure Swing Adsroption (PSA) technology. The result of concentration made is 33,4% for syntetic zeolite, 30% for silica gel, natural zeolite 20%, and activited carbon by 26,7%.